Modeling nonlinear road traffic networks for junction control - Péter, Tamás (Zielona Góra: Uniwersytet Zielonogórski)
The paper introduces a method of mathematical modeling of high scale road traffic networks, where a new special hypermatrix structure is intended to be used. The structure describes the inner?inner, inner?outer and outer-outer relations, and laws of a network area. The research examines the nonlinear equation system. The analysed model can be applied to the testing and planning of large-scale road traffic networks and the regulation of traffic system
Keywords: mathematical modeling and control; traffic networks; nonlinear positive system; linear Lyapunov function